Efficiency determination of the method "special lane in the intersection area" from the standpoint of priority in time - Вікович, Ігор Андрійович; Зубачик, Роман Михайлович; Беспалов, Дмитро Олександрович (Technology audit and production reserves, 2014)
Using the space-time priority and priority in time at the isolated signal-controlled intersection with one traffic lane on all approaches is considered in the paper. Space-time priority is represented by the method “special lane in the intersection area”, which in this case is a combination of a special lane in the intersection area and adaptive algorithm for a special phase call. Priority in time is realized using the algorithm for continuation of the enable signal and early termination of the disable signal. Using VISSIM software, the efficiency of these algorithms under different traffic conditions at the intersection is determined. The most effective application scope of the method “special lane in the intersection area”, where priority in time is implemented using the algorithm for the special phase call is defined